EVALUASI PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PERDESAAN DI DESA WARUKAPAS KECAMATAN DIMEMBE - Jessie F. Tilung; Joachim N.K. Dumais; Caroline B.D. Pakasi; Ribka M. Kumaat (COCOS, 2014)
ABSTRACTJessie Tilung. Rural Agribusiness Enterprise Development Program Evaluation In Warukapas Village, Dimembe Sub District. Under the guidance of Joachim. N. K. Dumais, as a chairman, B. C. D. Pakasi, and R. M. Kumaat as member’s.The objective of this research in to describe the evaluation of rural agribusiness enterprise development programs, based on outputs, outcomes, benefits, impact. This research was conducted in Warukapas Village, Dimembe Sub District North Minahasa Regency, lasted from June 2013 to March 2014. Data collected in this study is primary data obtained from questionnaires that have been presented to farmers PUAP funds and in-depth interviews (Indepth Interviews) to parties involved in the implementation of the program include administrators Gapoktan PUAP Esa Toroan and accompanying companion extension Gapoktan, while secondary data was obtained from agencies involved in this study that the data related to the program PUAP, Warukapas Village Office, Gapoktan Secretariat and the Central Bureau of Statistics.Sampling was done intentionally using simple random sampling and samples taken as many as 15 farmers who were PUAP’s receiver Gapoktan members of Warukapas Village, Dimembe Sub District North Minahasa Regency.The research result showed that PUAP programs provided by the government at the Warukapas Village especially Gapoktan Toroan Esa has gone well by lookingat funds that have been distributed to the who need, the increase of agribusiness activity, increased revenue from Rp. 15,446,403, after receiving PUAP, the increased of an average value of Rp. 20,927,239, PUAP programs provided by the government gave a positive impact for the community, therefore the active role of the community is expected to support government programs that would be useful for the community itself.